DC-Bus Voltage Control Based on Power Flow Management Using Direct Sliding Mode Control for Standalone Photovoltaic Systems. Issue 10 (15th June 2017) - Ameur, Khaled; Hadjaissa, Aboubakeur; Cheknane, Ali; Essounbouli, Najib
Abstract: Standalone PhotoVoltaic System (SPVS) performance is heavily dependent on the DC-bus voltage. A robust control of the DC-bus voltage results in a good stable-working system. This paper presents a new strategy, of controlling the different elements of the system, that helps to regulate the DC-bus voltage against abrupt load variation, and keeps the system working effectively even during the lack of batteries. It uses Sliding Mode Controllers (SMC) for DC-DC converters to improve the dynamic performance of the PV system. It protects the batteries by using them only when they are needed, and therefore extends the lifetime of the installation. The system is designed to supply both DC and AC loads in remote sites where no grid utility is available. It is composed of three photovoltaic arrays, a bank of batteries, a set of DC-DC and DC-AC converters, and DC/AC loads. The operations of the system are categorized into 04 modes, and their selection depends on the supply and demand of energy on one side, and the state of charge of the batteries on the other. The system is modeled and simulated in Simulink environment. Tests are done under very hard and quick variations of load, and results bear witness to the robustness of the controllers and to the high performance of the system as well.